A healthy degree of suspicion: A discussion of the implementation of transmission based precautions in the emergency department. Issue 3 (August 2016) - Zimmerman, Peta-Anne; Mason, Matt; Elder, Elizabeth
Summary: Background: Emergency department (ED) presentations have increased significantly domestically and internationally. Swift identification and implementation of transmission based precautions (TBP) for patients known or suspected of having an epidemiologically important pathogen is important. ED staff, particularly triage nurses, are pivotal in detecting and preventing infection, including healthcare associated infections (HAI). Methods: MEDLINE, CINAHL, PubMed and Ovid were searched for articles published between 2004 and 2015 using key search terms: infection control/prevention and emergency department(s), triage, and transmission based precautions and emergency department(s), and triage, to identify common themes for discussion. Systematic review/meta-analysis was not in the scope of this exploration. Findings: Themes were identified relating to HAI and ED practices and grouped into: assisted detection of conditions for which TBP is required, ED and TBP, mass-causality event/bioterrorism/pandemic/epidemic, infection control not TBP and multi-resistant organisms not TBP. The literature is heavily influenced by worldwide epidemic/pandemics and bioterrorist risks resulting in increased awareness of the importance of swift identification of syndromes that require TBP, but only in these situations. Conclusion: Implementation of appropriate TBP, changing triage practices, training and measures to assist decision-making could assist in preventing HAI in the ED context. A systematic quantitative review of the literature is recommended to guide practice change research.